Deseo de engendrar y de dar a luz en lo bello: La estructura de Eros en el discurso de Diotima y su relación con la generación de conocimiento - García Carrera, Gabriel Arturo (PLATO JOURNAL, 2020)
This paper aims to analyze Diotima’s definition of eros as a desire to beget and give birth in beauty. The main problem lies in the use of the notions of kuêsis, tokos, genesis and gennêsis. We will distinguish the meanings of each term and show that the erotic relationship is focused on the preservation of that which the lover already carries within himself. On this basis, and by using some passages from the Phaedrus, we seek, finally, to explain why science belongs to the realm of generation.